A Novel Treatment With Obinutuzumab-Chlorambucil in a Patient With B-Cell Prolymphocytic Leukemia: A Case Report and Review of the Literature. (13th July 2018) - Hew, Jason; Pham, Dat; Matthews Hew, Trevanne; Minocha, Vinay
We report the case of a patient with B-cell prolymphocytic leukemia who was successfully treated with the novel humanized monoclonal antibody obinutuzumab. This patient was previously treated with the combination of rituximab and bendamustine and had recurrent infusion reactions. Her treatment with rituximab and bendamustine was discontinued when she developed disease progression after 3 cycles of therapy. She was then treated with obinutuzumab 1000 mg on day 1 of every cycle and chlorambucil 0.5 mg/kg on days 1 and 15 every 28 days to which she had greater tolerability. After 4 cycles of treatment, she had resolution of her clinical symptoms, massive splenomegaly, and normalization of her white blood cell count.